SOX4 and RELA Function as Transcriptional Partners to Regulate the Expression of TNF- Responsive Genes in Fibroblast-Like Synoviocytes - Jones, Kyle; Ramirez-Perez, Sergio; Niu, Sean; Gangishetti, Umesh; Drissi, Hicham; Bhattaram, Pallavi (Frontiers in Immunology, 2022)
SOX4 belongs to the group C of the SOX transcription factor family. It is a critical mediator of tumor necrosis factor alpha (TNF)-induced transformation of fibroblast-like synoviocytes (FLS) in arthritis. In this study we investigated the genome wide association between the DNA binding and transcriptional activities of SOX4 and the NF-kappB signaling transcription factor RELA/p65 downstream of TNF signaling. We used ChIP-seq assays in mouse FLS to compare the global DNA binding profiles of SOX4 and RELA. RNA-seq of TNF-induced wildtype and SoxC-knockout FLS was used to identify the SOX4-dependent and independent aspects of the TNF-regulated transcriptome. We found that SOX4 and RELA physically interact with each other on the chromatin. Interestingly, ChIP-seq assays revealed that 70.4% of SOX4 peak summits were within 50bp of the RELA peak summits suggesting that both proteins bind in close-proximity on regulatory sequences, enabling them to co-operatively regulate gene expression. By integrating the ChIP-seq results with RNA-seq from SoxC-knockout FLS we identified a set of TNF-responsive genes that are targets of the RELA-SOX4 transcriptional complex. These TNF-responsive and RELA-SOX4-depenedent genes included inflammation mediators, histone remodeling enzymes and components of the AP-1 signaling pathway. We also identified an autoregulatory mode of SoxC gene expression that involves a TNF-mediated switch from RELA binding to SOX4 binding in the 3’ UTR of Sox4 and Sox11 genes. In conclusion, our results show that SOX4 and RELA together orchestrate a multimodal regulation of gene expression downstream of TNF signaling. Their interdependent activities play a pivotal role in the transformation FLS in arthritis and in the inflammatory pathology of diverse tissues where RELA and SOX4 are co-expressed.